(Self-) infections with parasites: re-interpretations for the present - Lukeš, Julius; Kuchta, Roman; Scholz, Tomáš; Pomajbíková, Kateřina (Trends in parasitology, 2014)
Previously, scientists sometimes resorted to infecting themselves or colleagues with parasites, usually to assess the pathogenicity and obtain insight into the life cycles of the parasites, host specificity, and epidemiology. However, with recent research addressing the possible beneficial impact of intestinal helminths on a range of immune-mediated diseases in humans, these studies offer valuable information, although many are now considered unethical owing to a lack of experimental oversight and informed consent. Here, we critically review cases in which humans were deliberately infected with parasites. Moreover, we summarize the contribution of (self-) infections and propose protist and helminth candidates, chosen on the basis of several criteria, to test as possible therapy for selected human diseases.
Keywords: helminth therapy; autoimunitní nemoci; parazitární nemoci; Host-Parasite Interactions; cizopasní červi; interakce hostitele a parazita; autoimmune diseases; Eukaryota; helminths; Parasitic Diseases; volunteers; protists; self-infection; Immune System Phenomena; Animals; lidé; Humans; zvířata; imunitní systém - jevy; Ethics, Medical; Autoimmune Diseases; Helminths; lékařská etika